DEVELOPMENT OF BIG-BOOK MEDIA ON EARLY READING LESSON AT GRADE I OF ELEMENTARY SCHOOL - Nurhasanah Nurhasanah; Febriana Dafit (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses developmental research. The aim of the research was to find out the validity of big-book media in early reading lessons for students in grade 1. The research was conducted at SDN 008 Gunung Mulya, SKPA street of Gunung Mulya, Mount Sahilan sub-district, Kampar in Riau Province. The stages of the research were modified analysis, design, and development of the ADDIE development model. The research indicates that the validity of the big book media is a very valid category without revisions. It is based on the result of validation by material experts, linguists, and design experts. In terms of the material aspect, the percentage is 96.87% with a very valid category. The language aspect indicates 92.50% with a very valid category. And the design aspect reveals 96.25% with a very valid category.Â Â